Enhanced in vivo Stability and Antitumor Efficacy of PEGylated Liposomes of Paclitaxel Palmitate Prodrug - Wu X; Wang X; Zhang H; Chen H; He H; Lu Y; Tai Z; Chen J; Wu W (International Journal of Nanomedicine)
Xin Wu,1– 3,* Xinyu Wang,3,* Haiyan Zhang,3,* Hang Chen,3,* Haisheng He,2 Yi Lu,1,2 Zongguang Tai,1 Jianming Chen,3 Wei Wu1,2 1Shanghai Skin Disease Hospital, School of Medicine, Tongji University, Shanghai, 200443, People’s Republic of China; 2School of Pharmacy, Fudan University, Key Laboratory of Smart Drug Delivery, Ministry of Education, Shanghai, 201203, People’s Republic of China; 3Shanghai Wei Er Lab, Shanghai, 201707, People’s Republic of China*These authors contributed equally to this workCorrespondence: Wei Wu, School of Pharmacy, Fudan University, Key Laboratory of Smart Drug Delivery, Ministry of Education, Shanghai, 201203, People’s Republic of China, Tel/Fax +86-21-64175590, Email wuwei@shmu.edu.cn Zongguang Tai, Shanghai Skin Disease Hospital, School of Medicine, Tongji University, Shanghai, 200443, People’s Republic of China, Tel/Fax +86-36803155, Email taizongguang@126.comPurpose: The clinical use of paclitaxel (PTX) in cancer treatment is limited by its poor water solubility, significant toxicity, and adverse effects. This study aimed to propose a straightforward and efficient approach to enhance PTX loading and stability, thereby offering insights for targeted therapy against tumors.Patients and Methods: We synthesized a paclitaxel palmitate (PTX-PA) prodrug by conjugating palmitic acid (PA) to PTX and encapsulating it into liposomal vehicles using a nano delivery system. Subsequently, we investigated the in vitro and in vivo performance as well as the underlying mechanisms of PTX-PA liposomes (PTX-PA-L).Results: PTX had a remarkable antitumor effect in vivo and significantly decreased the myelosuppressive toxicity of PTX. Moreover, the introduction of PA increased the lipid solubility of PTX, forming a phospholipid bilayer as a membrane stabilizer, prolonging the circulation time of the drug and indirectly increasing the accumulation of liposomes at the tumor site. Our in vivo imaging experiments demonstrated that PTX-PA-L labeled with DiR has greater stability in vivo than blank liposomes and that PTX-PA-L can target drugs to the tumor site and efficiently release PTX to exert antitumor effects. In a mouse model, the concentration of PTX at the tumor site in the PTX-PA-L group was approximately twofold greater than that of Taxol. However, in a nude mouse model, the concentration of PTX at the tumor site in the PTX-PA-L group was only approximately 0.8-fold greater than that of Taxol. Furthermore, the originally observed favorable pharmacodynamics in normal mice were reversed following immunosuppression. This may be caused by differences in esterase distribution and immunity.Conclusion: This prodrug technology combined with liposomes is a simple and effective therapeutic strategy with promising developmental prospects in tumor-targeted therapy owing to its ability to convert PTX into a long-circulating nano drug with low toxicity, high pharmacodynamics, and good stability in vivo.Keywords: paclitaxel palmitate liposome, prodrug, membrane stabilizer, esterase metabolism, Immunity